Assessment of sleep quality in patients with severe asthma - Joana Sofia Pereira de Magalhães Ferreira (2021)
Study objectives: The main objective of this study was to assess the sleep quality of patients with severe asthma. Additionally, we aimed to identify predictors of obstructive sleep apnea (OSA) in severe asthmatic patients, as well as evaluate the prevalence of OSA in patients with severe asthma. Methods: 57 patients with severe asthma were enrolled in this observational study. Pre-determined variables were collected through the database of each patient and a polysomnography was performed in 32 of the selected patients. Mann-Whitney U, Kruskal Wallis and Multiple Regression Tests were conducted to address the study goals. Results: From the selected patients, 56.3% had sleep apnea, defined by an AHI > 5 in the polysomnography; mean sleep efficiency (%) was 81.37 ± 10.84, median REM sleep time was 11.60%, and the median time of deep sleep was 16.20%. The serum eosinophils levels showed to be statistically significant in predicting the AHI (p < 0.05): for each unit increase in the serum eosinophils there is a decrease in AHI of 0.062 events/h. The biologic therapy also showed to be statistically significant in predicting the AHI (p < 0.05): patients who undergo this therapy have 15.69 more events/h compared to those who do not. Conclusions: More than half of the patients with severe asthma were diagnosed with sleep apnea. This study showed that there are no reliable predictors for this diagnosis, indicating that a polysomnography evaluation should be considered in every severe asthmatic patient. Keywords: severe asthma, obstructive sleep apnea, sleep quality